RFID lecturer availability system - Abdullah, Zeyana; Soosay Nathan, Shelena (Penerbit UTHM, 2020)
In process of learning in polytechnic, having a meeting with a lecturer was an importance thing to make sure that all the task given are clearly understand and submitted on time. As such, RFID Lecturer Availability System (L.A.S) will enable to identify the availability of the lecturer for the students. This will enable the students to get inputs if the lecturer is available or having different work to be done. The advantage of LAS is that it is easy to be used and low costs. This enable an efficient product to ensure students are aware of lecturer availability before commencing any meetings or appointment. In future, the study will focus on the evaluation of the prototype in measuring the usefulness of the application developed.